Agriculture teachers' competence on skill acquisition among students with auditory processing disorder - Abba, Umar Musa; Mat Rashid @ Mat Idris, Abdullah; Asimiran, Soaib (Human Resource Management Academic Research Society, 2019)
The inclusion of students with learning disability in regular classroom settings has been identified worldwide as essential to the provision of effective education for all and the creation of a more accessible environment. There have been few empirical studies in developing countries on teachers’ competence to educate students with specific learning disabilities in an accessible environment. This study aimed to explore the influence of agricultural science teachers’ competence on skill acquisition among students with auditory processing disorder. Different types of teachers’ competence were examined, including methodological competence, motivational competence, material utilization competence, and teaching evaluation competence. The study employed a cross-sectional survey design with a multi-stage cluster sampling technique. A survey instrument was developed and distributed to 237 agriculture teachers in Nigeria that were asked about their perception on teachers’ competence in inclusive education in providing agricultural skills and support for students with auditory processing disorder. Therefore, the agriculture teachers were asked to complete the questionnaires given one week. Data revealed that the agriculture teachers reported moderate level of teachers’ competence for teaching students with auditory disorder in inclusive school settings. Implications of these results include the need for further investigation into the training needs of agriculture teachers regarding competencies for inclusive education practices, such as differentiation and universal design for learning to promote social justice.